Digital Archive on Agricultural Theses and Journals (DAATJ) of Bangladesh: An overview - Bhuiyan, Mohammad Shakaought Hossain (Cadernos BAD, 2020)
The purpose of this paper is to investigate the current status, potential benefits and challenges of digital archiving of agricultural theses and journals in Bangladesh with a focus on the lesson learnt from a World Bank financed project titled as ‘Digital Archive on Agricultural Theses and Journals of Bangladesh’. That project worked on the three Bangladeshi Agricultural Universities for five years with an aim to convert all the printed Master of Science (MS) and Doctoral theses to digital format. Following a qualitative methodology, this study was conducted through an intensive review of project documents as well as consultation with educators and students. Results of the study reveals the prospect and challenges of establishing ETD repositories for agricultural universities in Bangladesh. The analysis indicate the value of project experiences for introducing a model of ETD repositories. With a policy implication, the findings reveals that academicians, researchers, librarians, students, policy makers, extension providers and farmers would get immense benefit from such archive. Observing the success, it is recommended to adopt similar model for other agricultural universities in Bangladesh. The findings may be are of values for establishing ETDs in other developing countries for disseminating knowledge